Public Evaluation of Speed Humps Performance and Effectiveness - Sayed Shwaly; Amal AL-Ayaat; Mohamed Hamed Zakaria (Civil Engineering Journal, 2018)
In Egypt, it is believed that speed humps are the cheapest and best solutions to reduce vehicles speed and thus reduce the number of potential accidents. Due to the lack of specifications in Egypt that govern the installation of speed humps, they were spread randomly and with different dimensions without adequate studies. Consequently, this practice can cause adverse effects on the road users and the surrounding environment. For this purpose, a questionnaire was designed to discuss the different effects of using speed humps in Kafr El-Sheikh city as a typical model in the Egyptian cities. To verify that the questionnaire is appropriate for the intended task, it was evaluated by 30 respondents aged 18 years and over. After the trial process, the required corrections were made to the proposed form of the questionnaire. Then, final questionnaires were distributed and 1000 responses were collected from all road users, whether they were pedestrians, drivers, owners of vehicles or vehicle repairmen by using face-to-face interviews. The responses were analysed using SPSS program. The results reflected that the installation of speed humps contributed greatly to reduce vehicles speed, the flow of traffic and accidents rate. On the other hand, the results proved that humps also contribute significantly to the environmental pollution, damage to the pavement and vehicles especially when they are poorly designed and located. The majority of respondents attributed the random spread of the speed humps to the weakness of the authorities in law enforcement and the prevention of the installation of new humps without authorization. Finally, with the widespread use of speed humps and with the exception of the positive impact on traffic safety, it also has negative impacts on both the economy and the environment. Finally, the use of speed humps can cause many harmful effects to the neighbourhood, if there no strict control on its installation process. Unless specifications and some standards should be strictly followed, other means of traffic calming measures should be considered.